Endovascular Treatment of Ruptured Intracranial Aneurysms: Factors Affecting Midterm Quality Anatomic Results: Analysis in a Prospective, Multicenter Series of Patients (CLARITY) - Pierot, L. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Recanalization is 1 drawback of the EVT of intracranial aneurysms. An analysis of the factors affecting the midterm anatomic results after EVT of ruptured intracranial aneurysms in a large multicenter series (CLARITY) is presented. MATERIALS AND METHODS: Of the 782 patients initially included in the CLARITY trial, 649 would theoretically undergo midterm follow-up examinations. Finally, 517/649 (79.7%) completed a midterm follow-up examination. Midterm anatomic results were independently and anonymously evaluated by 2 experienced neuroradiologists. RESULTS: In univariate analysis, factors affecting the quality of midterm occlusion were the quality of the postoperative occlusion (P < .001), hypertension (P = .018), aneurysm size (P = .007), neck size (P = .005), and ICA location (P = .049). In multivariate analysis, 3 factors were associated with the quality of postoperative aneurysm occlusion: neck size (P = .003), use of the balloon remodeling technique (P = .031), and the quality of postoperative occlusion (P < .001). In univariate analysis, the evolution of aneurysm occlusion was affected by age (P = .024) and neck size (P = .041). In multivariate analysis, it was associated with the same factors: age (P = .025) and neck size (P = .043). CONCLUSIONS: Among the many factors considered in this analysis, aneurysm neck size was identified as the single most important one in the quality of aneurysm occlusion at midterm follow-up after EVT. The present results suggest developing and evaluating new strategies of treatment and technique, especially for wide-neck aneurysms, with a focus on reinforcement and neoendothelialization at the level of the neck as objectives.